The Influence of the Number of Threads on the Archimedes Screw Turbine Prototype for Green and Renewable Energy Generation - Eva Kurnia Yulyawan; Indro Wicaksono; Indah Noor Dwi Kusuma Dewi; Ahlan; Wahyu Nur Achmadin (Universitas Panca Marga, 2022)
Energy needs in Indonesia are currently still dominated by energy based on fossil fuels, such as oil and coal. The disadvantage of fossil fuels is that they are not environmentally friendly. Water is an alternative energy source that can replace fossil-based energy sources and is a renewable energy. The Archimedes Screw turbine is a turbine suitable for use in Indonesia which has a low head river flow.This research uses an experimental method, namely designing and manufacturing an Archimedes Screw turbine. The results of the 180 minute test of the three Archimedes screw turbine models, namely threads screw type 1 produces a voltage of 2.83 volts, screw type 2 produces a voltage of 3.16 volts and screw type 3 produces a voltage of 2.49 volts. Thread type 2 which can produce a greater voltage for 180 minutes, which is 3.16 volts.